A review of the Costa Rican myxomycetes (Amebozoa) - Rojas Alvarado, Carlos Alonso (2010)
There has not been a comprehensive review of the taxonomic composition of the assemblage of myxomycetes known from Costa Rica since 1975. As a result of a series of studies carried out in the country during the last decade, considerable additional data now exist, and the review presented herein provides an update on this group of organisms. Collecting carried out in Costa Rica since 1975, a review of the published literature, and an examination of herbarium specimens were used to generate an annotated list consisting of a total of 208 species in 36 different genera. This includes 62 species not previously reported from Costa Rica. The relative abundance of the different orders follows the expected distribution for the Neotropics, with the order Physarales being the most abundant. Interestingly, the data also show that the distribution of species is highly heterogenous. This result suggests that most myxomycetes in Costa Rica are highly specialized for certain microhabitats defined by macro- and microenvironmental factors.